2016
DOI: 10.1007/s12041-016-0683-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in barley landraces (Hordeum vulgare L. subsp. vulgare) originated from Crescent Fertile region as detected by seed storage proteins

Abstract: Genetic diversity in barley landraces (Hordeum vulgare L. subsp. vulgare) originated from Crescent Fertile region as detected by seed storage proteins. J. Genet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Similarly [13] total of 22 barley landraces was collected from different farmers for agro morphological evaluation 3 parameter which show high variation in spike length, spike colour and spike type, but in case of spike length, it show high variability in spike length (70%) from 5 to 9 cm. [14] it was investigate the same result which was related to the present study because for morphological characterization it was take the same both qualitative and quantitative traits which show similarities and variation like present study, especially in kernel covering.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Similarly [13] total of 22 barley landraces was collected from different farmers for agro morphological evaluation 3 parameter which show high variation in spike length, spike colour and spike type, but in case of spike length, it show high variability in spike length (70%) from 5 to 9 cm. [14] it was investigate the same result which was related to the present study because for morphological characterization it was take the same both qualitative and quantitative traits which show similarities and variation like present study, especially in kernel covering.…”
Section: Discussionsupporting
confidence: 57%
“…Scatter plot were also draw through this software which show significant variation the closely related genotype present in the same axis in cluster form. [14] Reported 37 bands in literature. Similarly [15] was also reported the same result for protein bands a total 12 was reported.…”
Section: Biochemical Assessmentmentioning
confidence: 99%
“…Additionally, when clustering and population structure analyses have been considered, the total genetic variation was higher within than between groups, and the groups were in general consistent with the geographical origin of the lines, except in a few cases. Mzid et al [ 64 ] assessed genetic diversity in a panel of 53 Lebanese barley landraces through the electrophoretic pattern of the seed storage proteins, hordeins. In this case, the absence of correlation between the genetic variability and the geographic origin of sample provenance was explained by the fact that Lebanon is a small country where seeds are easily exchanged between farmers’ communities in the different regions.…”
Section: Exploration Of Genetic Diversity and Population Structurementioning
confidence: 99%
“…Another botanist (Baloch et al, 2014) worked on 90 genotypes of barley and observed 20 bands. (Mzid et al, 2016) also reported 37 bands in his research on barley landraces. In the present study, a high level of variation was observed in B26 (0.98%) and B25 (0.89%).…”
Section: Discussionmentioning
confidence: 91%